Hubungan Intensitas Penerangan Dengan Kelelahan Mata Pada Pekerja Shift Malam Bagian Daily Check Di PT. Kereta Api Daerah Operasi VI Yogyakarta Dipo Kereta Solo Balapan - Barleanty, Dwiky Isnandia, SrI Darnoto, SKM.,M.PH (2016)
Lighting intensity which does not meet the standard can cause potential of eyes exhaustion. Jobs of checking and repairing the railway coach are included in kinds of job which need carefulness, therefore, the jobs need a lighting intensity which is appropriate to the standard that is 100 lux. Lighting intensity which does not meet the standard results in the occurence of a complaint about eyes such as red eyes, headache, and irritated eyes. This research aims to know the correlation between the lighting intensity and the eyes exhaustion in the night-shift employees of daily check division in PT. Kereta Api Daerah Operasi VI Yogyakarta DIPO Kereta Solo Balapan. Type of this research is observasional analitical using cross sectional approach. Samples of the research are as many as 72 people from total of population of 72 people who are divided into the morning shift, the daylight shift, and the night shift as many as 24 employees each. Every night-shiftemployee has three times of shift change in a week with a different day. The technique of sampling used in this research is Exhaustive Sampling. The independentvariable in this research is the lighting intensity, meanwhilem the dependent variable in this research is the eyes exhaustion. The analysis of this research used Chi-Square test which revealed that there is correlation between the lighting intensity and the eyes exhaustion in the night-shift employees of daily check division in PT. Kereta Api Daerah Operasi VI Yogyakarta DIPO Kereta Solo Balapan (p value = 0.001 <0.05). Keywords : Eyes Exhaustion, Lighting Intensity Literature : 37, 1992-2016